Fable Puppet Show as an Alternative Communication Media Moral and Character Education of Elementary School Students - Noegroho, Jati; Sovia Firdaus, Dwi Rini (Universitas Negeri Padang, 2024)
Wayang Beber is one of Indonesia's cultural heritages, and it contains moral values relevant to children's character education. This research aims to explore the effectiveness of Wayang Beber Fabel as a visual communication medium in character education for elementary school students, as well as contributing to the preservation of local culture. The research uses a qualitative phenomenological approach. The method involves participant observation, in-depth interviews, and document analysis as data collection techniques. The research subjects included elementary school students and teachers who used Wayang Beber Fabel media in teaching and learning activities. Data analysis was done using thematic methods to understand student responses and identify challenges in implementing this media in the elementary school environment. The research results show that Wayang Beber Fabel can attract students' interest and deepen their understanding of character values such as honesty, responsibility and tolerance. Hopefully, this research will also contribute to character education in Indonesia by presenting local culture-based media that can be integrated into the elementary school curriculum. It is hoped that the findings of this research can promote the use of traditional art as an educational instrument. Not only does it support learning in schools, but it also strengthens national cultural identity.